Culture, Technology, and Tourism (CTT) Theory: An Ontological Perspective - Ardianto, Eka (Prasetiya Mulya Publishing, 2019)
Author argues that Culture, Technology, and Tourism (CTT) is an integrated multidisciplinary. Therefore, author explores dimensionality of CTT Theory from various perspective. The results are: 1) local wisdom is the essence of the authenticity of cultural heritage; 2) local community as the actor should has the role to protect environment in order to ensure sustainability of tourism; 3) multistakeholder network should be managed as a pattern of complexity that characteristic of an integrated multidisciplinary; 4) creative economy and sociopreneurship as the enabler and driver of tourism entrepreneurship to ensure sustainability of tourism; 5) smart tourism that leverage the technology should be constructed through destination management in order to ensure sustainability of tourism and the authenticity of tourism; and 6) body-mind and hedonic-eudaimonic should be integrated to manage tourist’s well-being. Refer to general system theory, author explains a CTT theory through relationship between those six results of dimensionality through input, process, output, and outcome relation.